3D flower-like hollow CuS@PANI microspheres with superb X-band electromagnetic wave absorption. (1st November 2022) - Zhao, Jia; Wei, Ying; Zhang, Yi; Zhang, Qingguo
Highlights: Novel 3D flower-like hollow CuS@PANI micropheres have been successfully synthesized via a solvothermal process followed by in-situ polymerization. The excellent reflection loss of 3D flower-like hollow CuS@PANI micropheres is −71.1 dB with a matching thickness of 2.75 mm. The effective absorption bandwidth of 3D flower-like hollow CuS@PANI micropheres almost cover the whole X-band. Abstract: Superior electromagnetic (EM) wave absorption properties in 8.2–12.4 GHz ( X -band) can be obtained via the effective combination of polyaniline (PANI) and CuS. Herein, novel 3D flower-like hollow CuS@PANI microspheres were fabricated by a solvothermal process followed by in-situ polymerization. EM wave absorption properties of 3D flower-like hollow CuS@PANI microspheres in X -band were systematically studied, indicating the minimum reflection loss ( RL min ) of -71.1 dB and effective absorption bandwidth (EAB) covering 81% of test frequency range were achieved with a thickness of 2.75 mm. Excellent EM wave absorption properties of 3D flower-like hollow CuS@PANI microspheres were mainly ascribed to outstanding impedance matching characteristic and dielectric loss capability (conduction loss, interfacial polarization loss and dipole polarization loss). Moreover, due to the distinctive flower-like hollow structure of CuS@PANI microspheres, an additional wave-absorbing mechanism was provided by increasing the transmission paths of EM waves.